The Analysis 0f Writing Science Communication Skills Reviewed From The Distribution of Students' Learning Styles of Grade X - Ramayanti; Nevrita; Hindrasti, Nur Eka Kusuma (The Future of Education Journal, 2024)
This study aims to analyze science communication skills in writing based on the distribution of learning styles. The research is a quantitative descriptive study. The population consists of 347 tenth-grade students, with a sample of 186 students. Sampling was conducted using stratified random sampling techniques. The instruments used include a portfolio sheet with practical reports and a learning style questionnaire. To analyze science communication skills in writing based on learning style distribution, the collected data were analyzed using descriptive statistical techniques with Microsoft Excel. The results show that the average science communication skills in writing, categorized by learning style, are rated as very good, with a percentage of 81%. This indicates that visual learning style dominates and significantly contributes to the science communication skills in writing among tenth-grade students at SMA Negeri 4 Tanjungpinang. In other words, students with a visual learning style demonstrate very good performance in written science communication